2021
DOI: 10.1007/s12369-021-00824-3
|View full text |Cite
|
Sign up to set email alerts
|

Social Robots for (Second) Language Learning in (Migrant) Primary School Children

Abstract: Especially these days, innovation and support from technology to relieve pressure in education is highly urgent. This study tested the potential advantage of a social robot over a tablet in (second) language learning on performance, engagement, and enjoyment. Shortages in primary education call for new technology solutions. Previous studies combined robots with tablets, to compensate for robot’s limitations, however, this study applied direct human–robot interaction. Primary school children (N = 63, aged 4–6) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Sixteen of the 83 studies (partly) targeted a migrant population (Kim et al, 2014;Gordon et al, 2016;Rosenthalvon der Pütten et al, 2016;Kory Westlund et al, 2017;Lopes et al, 2017;Hemminki and Erkinheimo-Kyllönen, 2017;Goossens et al, 2019;Park et al, 2019;Engwall and Lopes, 2020;Kouri et al, 2020;Schulz et al, 2020;Engwall et al, 2021;Halbach et al, 2021;Leeuwestein et al, 2021;Cumbal, 2022; A robot mostly speaking L2, but also translating target words to L1 Konijn et al, 2022). A striking result is that only one of these studies used students' L1 to support learning of the L2 (Leeuwestein et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen of the 83 studies (partly) targeted a migrant population (Kim et al, 2014;Gordon et al, 2016;Rosenthalvon der Pütten et al, 2016;Kory Westlund et al, 2017;Lopes et al, 2017;Hemminki and Erkinheimo-Kyllönen, 2017;Goossens et al, 2019;Park et al, 2019;Engwall and Lopes, 2020;Kouri et al, 2020;Schulz et al, 2020;Engwall et al, 2021;Halbach et al, 2021;Leeuwestein et al, 2021;Cumbal, 2022; A robot mostly speaking L2, but also translating target words to L1 Konijn et al, 2022). A striking result is that only one of these studies used students' L1 to support learning of the L2 (Leeuwestein et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas this example refers to a change in robot’s role from one learning session to another, a change can also take place during one session, when interaction partners become more familiar with each other. This familiarization process, in turn, is influenced by individual differences in children ( Tolksdorf et al, 2021b ; Konijn et al, 2022 ). These plausible dynamics are barely in focus in current research, nor in our review.…”
Section: Discussionmentioning
confidence: 99%
“…• The third type of children that can be considered more sensitive for the robot's interaction, as indicated by two teachers, are children who are underachievers on a certain subject, such as language learning or math. Studies indeed reported good results for language learning (Vogt et al, 2019;Konijn et al, 2021) or rehearsing the times tables (Konijn and Hoorn, 2020). • The fourth and final type of children who are more sensitive to social robots are children with special needs, such as children with attention deficit hyperactivity disorder (ADHD), highly sensitive children, highly gifted children, and children sensitive to game addiction.…”
Section: Attachmentmentioning
confidence: 94%
“…Social robots are gradually being introduced in primary education. They provide new opportunities for improving cognitive outcomes, such as learning a second language (Vogt et al, 2019;Konijn et al, 2021), rehearsing the times tables (Konijn and Hoorn, 2020), learning sign language (Luccio and Gaspari, 2020) and training handwriting (Aktar Mispa and Sojib, 2020). In addition, social robots are used to support motivational and affective elements of learning (e.g., the learner being attentive, receptive, responsive, reflective, or inquisitive) (Belpaeme et al, 2018).…”
Section: Introductionmentioning
confidence: 99%